Penghilangan Padatan Tersuspensi Pada Pengolahan Air Limbah - Hendartini Hendartini (Jurnal Kimia dan Kemasan, 1995)
The main purpose of waste water treatment is to remove BOD and Suspended Solid. Many kinds of treatment can be applied in waste water depend on their characteristics. Among others are Sedimentation and Flotation. Sedimentation is the removal of solid particles from a suspension by gravitational settling in waste water treatment plants, sedimentation is applied to a variety of organic and inorganic solids from raw and treated waste. Meanwhile, the major waste water applications of flotation are thickening of activated and coagulated sludges which have densities close to water. Primary sedimentation basins generally remove 40 - 65 % of suspended solids and 25-50 % of BOD. Results from several flotation fasilities operating with waste activated sludge and chemical addition indicate an average solids removal near 98 % .